Zinc Oxide Nanoparticle Synthesize by Green Approach - Rashid, Muhamad Fariza; Ainuddin, Ainun Rahmahwati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Zinc oxide has been widely investigated by many researchers due to their potential opto-electric devices. This review was implemented to prepare ZnO nanoparticles using green synthesis method and to investigate the characteristic of ZnO nanoparticles with different reaction temperature and reaction time. There are several methods to prepare the ZnO nanoparticles. For this review, ZnO nanoparticles are synthesize by using different type of leaf extract. Characterization process of ZnO nanoparticles was described by using a XRD, UV-vis and photocatalytic activity to study the effect of nanoparticles of ZnO, characteristic morphological with different reaction temperature and time.